Highly active and reusable catalyst from Fe-Mg-hydrotalcite anionic clay for friedel-crafts type benzylation reactions - Choudhary, Vasant R.; Jha, Rani; Choudhari, P. A. (Journal of Chemical Sciences, 2005)
Fe-Mg-hydrotalcite (Mg/Fe = 3) anionic clay with or without calcination (at 200-800 degrees C) has been used for the benzylation of toluene and other aromatic compounds by benzyl chloride. Hydrotalcite before and after its calcination was characterized for surface area, crystalline phases and basicity. Both the hydrotalcite, particularly after its use in the benzylation reaction, and the catalyst derived from it by its calcination at 200-800 degrees C show high catalytic activity for the benzylation of toluene and other aromatic compounds. The catalytically active species present in the catalyst in its most active form are the chlorides and oxides of iron on the catalyst surface.
Keywords: activation by calcinations; benzylation of aromatic compounds; benzylation of toluene; Fe-Mg-hydrotalcite

High-temperature stable and highly active/selective supported NiCoMgCeOx catalyst suitable for autothermal reforming of methane to syngas - Choudhary, Vasant R.; Mondal, Kartick C.; Mamman, Ajit Singh (Journal of Catalysis, 2005)
Low-surface-area, macroporous, zirconia-haffnia-supported NiCoMgOx and NiCoMgCeOx (Ni/Co/Mg/Ce = 1/0.2/1.2/0.0 or 1.2) catalysts, precalcined at high temperature ( 1400 degrees C for 4 h), showed both high activity (> 98% conversion) and selectivity ( > 95%) in the catalytic partial oxidation of methane (CPOM) to syngas. Their performance remained unchanged even after they were subjected to higher temperature (> 2000 degrees C for 30 min) or a number of high-temperature (> 2000 degrees C) shocks, due to their direct exposure to an oxyacetylene flame. The supported NiCoMgCeOx, however, showed superior performance in the steam and CO2 reforming reactions because of its much higher lattice oxygen mobility. Hence it is more suitable for the autothermal reforming of methane. (c) 2005 Elsevier Inc. All rights reserved.
Keywords: autothermal reforming of methane; Catalyst; catalytic partial oxidation of methane; CO2 reforming of methane; high-temperature stable supported NiCoMgCeOx catalyst; steam reforming of methane; zirconia-haffnia-supported NiCoMgCeOx catalysts; zirconia-haffnia-supported NiCoMgOx

Hydrogen peroxide formation in the interaction of oxygen with boron-containing Pd catalysts prereduced by hydrazine in aqueous acidic medium containing bromide anions - Choudhary, Vasant R.; Samanta, C. (Catalysis Letters, 2005)
Interaction of molecular oxygen with Pd/BPO4 or ZrO2 (or Al2O3, CeO2, TiO2) - B2O3 catalysts, prereduced by hydrazine hydrate, in an aqueous acidic (H2SO4 or H3PO4) reaction medium containing bromide ions leads to the formation of H2O2. However, in the absence of boron in the catalyst and also in the absence of acid and/or bromide ions in the reaction medium, almost no H2O2 is formed.
Keywords: boron-containing Pd catalysts; Hydrogen peroxide; oxygen-catalyst interactions

Hydrogenation of hydrogen peroxide over palladium/carbon in aqueous acidic medium containing different halide anions under static/flowing hydrogen - Choudhary, Vasant R.; Samanta, Chanchal; Jana, Prabhas (Industrial & Engineering Chemistry Research, 2007)
Kinetics of the hydrogenation of hydrogen peroxide (at 278 and/or 300 K) over Pd(5 wt%)/carbon in aqueous medium with or without containing acid or different halide anions (F-, Cl-, Br-, or I-) under static H-2 (i.e. batchwise) or flowing H-2 (i.e. semi-batchwise) at atmospheric pressure have been thoroughly studied. In the absence of protons or halide anions and also in the presence of F- anions, a very rapid decomposition of H2O2 (H2O2 -> H2O + 0.5O(2)) predominates over the H2O2 hydrogenation (H2O2 + H-2 -> 2H(2)O). However, in the presence of both the protons and Cl- or Br- anions, the H2O2 conversion occurs mainly by the hydrogenation reaction. The hydrogenation is found to be a zero-order reaction with respect to the H2O2 concentration, and its activation energy and frequency factor are strongly influenced by the halide anions. The hydrogenation is found to be more and more inhibited with increasing halide (Cl- or Br-) anion concentration. The cations associated with the halide anions have, however, only a very little influence on the hydrogenation. Iodide anions act as a very strong catalyst poison for the hydrogenation. In the presence of acid, the hydrogenation is very strongly influenced by the different halides, but, in the presence of halide anions (5.4 mmol/dm(3)), it is very mildly influenced by the different mineral acids (except HI). In the absence of protons, the Cl- and Br- anions are ineffective for inhibiting the rapid H2O2 decomposition. A role played by protons and halide anions for drastically inhibiting the rapid H2O2 decomposition is discussed.

Highly efficient catalyst derived from Ni-Fe-hydrotalcite for solvent-free O- or S-acetylation of alcohols, phenols and thiols at room temperature - Choudhary, Vasant R. (Proceedings of the National Academy of Sciences India Section A-Physical Sciences, 2013)
Solvent-free O-acetylation of alcohols (including secondary and tertiary alcohols) and phenols and S- acetylation of thiols by acetyl chloride with high product yields at room temperature in a very short reaction period can be easily accomplished using a small amount of solid catalyst obtained from the decomposition (at 600 A degrees C) of Ni-Fe-hydrotalcite. Both the reactions are carried out at room temperature under solvent-free conditions. The catalyst can be easily separated from the reaction mixture, simply by filtration and reused several times without a significant loss of its activity.
Keywords: Acetyl chloride; Alcohols; Ni-Fe- ht derived catalyst; O- and S-acetylation; Phenols; Solvent-free